Strategi Masyarakat Gampong Iboih dalam Pengembangan Pariwisata Kota Sabang - Wilda Rahmi; Ibnu Phonna Nurdin; Khairulyadi Khairulyadi; Nurul Fajri (Politeknik Kampar, 2025)
Following the COVID-19 pandemic, the tourism sector in Gampong Iboih, Sabang City, has experienced a very encouraging recovery. This is marked by an increase in visits by both domestic and international tourists, as well as the winning of various awards at the national and ASEAN levels. This success is inseparable from the active involvement of the community in independently reviving tourism activities. This study aims to analyze community strategies in post-pandemic tourism development using a descriptive qualitative approach. Informants in this study included the Keuchik (village head), administrators of the Tourism Awareness Group (Pokdarwis), the Sabang City Tourism Office, local business actors, the general public, and domestic and international tourists. Data collection techniques were carried out through direct observation, in-depth interviews, and documentation. The results show that the strategies implemented by the Gampong Iboih community align with the four functions in Talcott Parsons' AGIL theory: adaptation, goal achievement, integration, and pattern maintenance. In terms of adaptation, the community is able to adapt to the needs and culture of tourists without losing their local identity. The development goal is reflected in efforts to make Iboih an orderly, friendly, and highly competitive tourist destination. Integration is evident in the synergy between business actors, the community, and the government in tourism management. Meanwhile, preservation of local culture is realized through the preservation of local culture, such as the Kenduri Laot tradition, education on traditional values, and enforcement of norms through a social approach. Thus, the community-based tourism development strategy in Gampong Iboih is not only practical but also reflects the successful application of AGIL theory as a social framework for sustainable and participatory tourism development.